WORKSHOP WORKSHOP ANALISIS BUTIR SOAL PADA DOSEN INSTITUT TEKNOLOGI PAGAR ALAM - Barrorotul Azizah; Risnaini Masdalipa; Debi Gusmaliza; Panyahuti Matondang (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2022)
Quality of Education has a relationship with the teaching system and evaluation system in order to monitor. So there must be a continuous continuous effort to improve the quality of education, because the demands for the quality of education are always changing according to the demands and developments of technological progress. Evaluation is a process of measurement and evaluation, both of which are closely related to the evaluation system. Measurement is a process of comparing systematically. Item analysis is a process activity to improve the quality of education, namely by analyzing items, it can be done by testing the quality of each item and a set of questions in various aspects, both qualitatively and quantitatively. The main purpose of item analysis is to obtain information about the characteristics of each item, either through item study or empirical analysis. The results can be used to determine the quality of questions and the quality of student learning from the analysis of test results. The item analysis carried out was using the CTT (Classical Test Theory) model item analysis with jMetrik, jMetrik is software that can be used to analyze the CTT model questions or the IRT model. This application was created and developed by J. Patrick Meyer, J Patrick Meyer is the copyright holder of jMetrik